2017
DOI: 10.3945/ajcn.117.156075
|View full text |Cite
|
Sign up to set email alerts
|

U-shaped curve for risk associated with maternal hemoglobin, iron status, or iron supplementation

Abstract: Both iron deficiency (ID) and excess can lead to impaired health status. There is substantial evidence of a U-shaped curve between the risk of adverse birth outcomes and maternal hemoglobin concentrations during pregnancy; however, it is unclear whether those relations are attributable to conditions of low and high iron status or to other mechanisms. We summarized current evidence from human studies regarding the association between birth outcomes and maternal hemoglobin concentrations or iron status. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
231
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(251 citation statements)
references
References 51 publications
14
231
2
4
Order By: Relevance
“…The highest correlations were evident with LBW, stunting in CU5 and overweight in adults. These correlations were similar for pregnant and non-pregnant women substantiating the findings of other workers (14) who showed that anaemia affects pregnancy outcome depending on the prepregnant and early pregnancy state of anaemia and although it increases during pregnancy, its ultimate outcome is determined by its prepregnant state (14) .…”
Section: (4)supporting
confidence: 87%
See 4 more Smart Citations
“…The highest correlations were evident with LBW, stunting in CU5 and overweight in adults. These correlations were similar for pregnant and non-pregnant women substantiating the findings of other workers (14) who showed that anaemia affects pregnancy outcome depending on the prepregnant and early pregnancy state of anaemia and although it increases during pregnancy, its ultimate outcome is determined by its prepregnant state (14) .…”
Section: (4)supporting
confidence: 87%
“…Trend analysis revealed a U-shaped curve (14) which correlates with the high rates of LBW in EMR. Hence iron supplementation may improve LBW especially in LIC.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations